(untitled) (Research, Society and Development, 2021)
Objectives: To verify the knowledge about potentially malignant lesions, to evaluate the oral health condition regarding the presence of potentially malignant lesions and to evaluate the quality of life. Methods: Cross-sectional study with a sample of 108 elderly people, with the application of questionnaires about the knowledge of potentially malignant lesions, mouth cancer, self-examination, quality of life and clinical examination. Results: Of the elderly, 3.7% knew what oral cancer is and 38.9% heard / read about potentially malignant lesions. Injuries were detected in 1.8% of the elderly. There were no significant differences in the GOHAI index. Correlating the presence of these injuries to the knowledge, of the individuals without injuries, 46.2% know what oral cancer is, those who presented injuries denied knowing the subject. In addition, 100% of the sample declared to have knowledge that alcohol/tobacco is related to oral cancer and 88,7% of the group of individuals who did not have potentially malignant lesions also agreed with this statement. Conclusion: There was a low level of knowledge and prevalence of potentially malignant oral lesions. Quality of life did not influence the presence or absence of injuries. Of the elderly people surveyed who had lesions, none could say what oral cancer is and 50% of those who did not have oral lesions demonstrated understanding about these disorders. Thus, the development of greater actions for the promotion and prevention of geriatric oral health, linked to clarifications regarding potentially malignant lesions and oral cancer, are remarkably essential.